The Secret of the Snow - Stilton, Thea; Heim, Julia; Facciotto, Giuseppe (Scholastic Inc., 2014)
Thea Stilton and her sisters journey to the land of Minwa, a realm linked to the legends of Japan and wrapped in mysteries and enchantments, to discover why the realm's special lotus flowers are disappearing--and why their diappearance seems to be threatening the whole land.
Keywords: Stilton, Thea; Juvenile fiction; Stilton, Thea; Fiction; Fiction; Adventure and adventurers; Fiction; Quests (Expeditions); Fiction; Lotus; Fiction; Juvenile fiction; Adventure stories; Juvenile fiction; Quests (Expeditions); Juvenile fiction; Lotus; Mice; Mice